IMMUNIZATION AGAINST MEASLES AND DIPHTHERIA IN CHILDREN WITH HIV - S.M. Kharit; L.M. Lianko; O.V. Goleva; A.S. Kvetnaya; S.V. Petlenko; E.P. Nacharova; N.F. Snegova ("Paediatrician" Publishers LLC, 2006)
The article presents the study of immunization with DTP vaccine (diphtheria, pertussis (whooping cough) and tetanus) in children from mothers with HIV and immunization against measles in 31 of them. The postvaccinal period was uneventful in most cases. The frequency of inter current illnesses (immunization complications) has been comparable with that in sickness prone children. The differences in the mean geometric values of antibody titresto diphtheria and measles between the HIV apositive children (group B23) and the hivanegative children from the mothers with HIV (group R75) have not reached the statistically significant levels. Meanwhile, the structure of measles antibody titre has shown that in HIV apositive children the protective antibodies were absent or reached the minimal level (1:5).Key words: children, HIV infection, anti measles immunization, anti measles antibodies.